Metagenomic, organoleptic profiling, and nutritional properties of fermented kombucha tea substituted with recycled substrates - Selvaraj, Suriyapriya; Gurumurthy, Kalaichelvan (Frontiers in Microbiology, 2024)
Kombucha fermentation yields a diverse range of beneficial macro and micronutrients. In our study, we examined the metabolites, antioxidant activity, organoleptic characteristics, and nutritional attributes of traditionally prepared kombucha tea, using black tea and sugar (control) as substrates, and compared them with tea made from tea dust and blackstrap molasses (test). Kombucha tea crafted from functional raw materials exhibited enhanced sensory qualities and improved health-promoting properties. The levels of tannins, flavonoids, and phenols play a crucial role in determining the antioxidant activity of kombucha tea. Using the DPPH and FRAP methods, we investigated the antioxidant activity throughout the fermentation period, ranging from day 0 to day 12, under optimized conditions. The results consistently demonstrated an initial increase in antioxidant activity from day 0 to 6, followed by a decline from day 6 to 12. Notably, statistical analysis revealed that the antioxidant activity of the test sample was significantly better (p > 0.001) compared to the control sample. The nutritional content of the kombucha from day 6 of the test sample is higher than the control sample provided sugars, minerals, vitamins, sodium, calories, carbohydrates. and acids on day 12. The predominant microbial species identified in both control and test samples included Komagataeibacter rhaeticus, Gluconobacter oxydans, Brettanomyces bruxellensis, and Zygosaccharomyces bailli, each with varying dominance levels. These microorganisms play essential roles in metabolizing sugars, generating acids, and contributing to the distinctive flavor profile of kombucha. Sensory evaluations of the control and test samples were analyzed, and the overall preference was 88% for the test sample with tea dust and molasses. The sensory characteristics of the test sample included a fruity smell (41%), fizzy texture (66%), bright color (47%), and a fruity taste (67%), with overall acceptability (56%) rating it as excellent. Our research contributes to a deeper understanding of the interplay between raw materials, microbial composition, and the resulting composition of bioactive compounds.